Exploring Consumers’ Decision-Making Process On Online Purchasing Of Health Supplements And Natural Products In Malaysia - Ang, Ju Ying (2024)
Health supplements and natural products are widely used by the general public to support physical function and prevent disease. Additionally, with the advent of ecommerce, these products have become easily accessible to the general public. Although several theoretical models have been used to explain the use of health supplements and natural products, empirical evidence on how consumers make decisions to purchase online health supplements and natural products remains limited. In this qualitative study conducted from january 2021 until march 2022, a grounded theory approach was used to develop a substantive theoretical model with the aim of exploring the decision-making process of consumers when purchasing health supplements and natural products online. Malaysian adult consumers who had purchased these products via the internet were either purposively or theoretically sampled. A total of 18 virtual in-depth interviews (idis) were conducted, each lasting between 30 to 80 min, with theoretical saturation achieved after all 18 idis. All the idis were audio-recorded and transcribed verbatim. The data were managed using nvivo 12 software, analysed using initial coding, focused coding and theoretical coding. Coding was performed by one researcher, and cross-checked by a second researcher, with any conflicts resolved via discussion with a third researcher to finalize the coding decisions. The analytical interpretations and theoretical concepts were recorded in research memos.